Speedy resolution of labour disputes in the interest of industry and economy of the country - Ali Mohamed, Ashgar Ali (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The paper argues that although the right to labour strike exists in Malaysia, it should not nevertheless be considered as an acceptable means of dispute resolution as this could ruin the national economy. It reveals the restrictions placed by the law in Malaysia before strike actions can be embarked upon. This notwithstanding the fact that labour strike has been an international phenomenon. It therefore recommends that speedy and peaceful resolution of labour dispute is in the interest of the industry and national economy.